Rainfall trends, land use change and adaptation in the Chaco salteño region of Argentina - Murgida, Ana Maria (2014)
Regional change under agricultural expansion in the Chaco of Argentina is determined by interactions of rainfall change, infrastructure development, socio-economic actions and values, and the social perceptions of change. Our study focused on adaptation in the socio-environmental system which is the key to understanding opportunities, uncertainties and risk in the context of historical change. Change in land use from extensive grazing through mixed farming and on to industrial-scale soybean production was made possible by a trend of increasing rainfall that reduced the risk of crop failure from drought since the 1970s. Rainfall change coincided with a period in which the Chaco forest was suffering extensive degradation from long-term extractive use. The degradation aided agricultural expansion since the degraded state of the ecosystem justified public policies of deforestation. In parallel to these resource-based processes, public policy changed in the late 70s and 80s toward favoring privatization of state land and exclusion of small producers. This permitted the land concentration needed for industrial-scale production. Technological innovation in both water and land resource management reinforced the process of concentration because small producers rarely have the financial or educational capital to develop or implement emerging technologies. One of the results of the intensification and expansion of agriculture is that soil surface sealing, waterlogging and flood risk are now effective at a landscape scale. To address these risks, private enterprise and government efforts must now come together toward innovative policies in integrated landscape management.